Electricity produced from citrus fruits and local fruits using kirchhoff’s second law / Nurul Suhada Aziz …[et al.] - Aziz, Nurul Suhada; Yusoff, Nur Ain Che; Azman, Fatin Nadzirah Izzatie; Mohd Judah, Sharifah Nor Faaiz Ibaa Syed (Universiti Teknologi MARA Cawangan Pahang, 2020)
The idea of using fruits as a battery has been discovered in the past. The reading of voltage and the current from the fruits were proven by using a multimeter. However, the value of the electrical current was computed in a mathematical way which was produced from the fruits. The purpose of this project is to determine which citrus and local fruits would produce the most electricity flow. The citrus and local fruits should contain high acidity content to conduct electricity and capable to be one of the power sources. This process can be applied to determine the number of citrus and local fruits required to power up a small application without conducting the real experiment. The estimated outcome of this experiment is the identification of the citrus and local fruits which could produce the highest electrical current. Perhaps using an Eco-friendly power source as a battery current might be convenient. The value of the electrical current was predicted by using a second differential equation in Kirchhoff’s Second Law method as from the accomplished result. The experiment was set up by the RLC series circuit which consists of an inductor, resistor, capacitor, and the citrus and local fruits as power sources.